Slovenska javna banka popkovnične krvi - Krašna, Metka (Farmacevtski vestnik, 2010)
The public cord blood bank is a non-profit organization that processes and stores donated unrelated cord blood for haematopoietic stem cell transplantations. In the past year and half, 833 women donated cord blood to our bank, of which 267 units (32%) were stored. In the past three months, an average of 80 parents per month donated cord blood and 24 units per month werecryopreserved. The median number of leukocytes per cord blood unit prior cryopreservation was 977 x 106 (n = 125; 507 x 106 - 2631 x 106). The mean recovery of leukocytes after processing the cord blood with the Sepax cell separation system was 74% (n = 44; 38 - 94%). We are planning to start the accreditation process at the international registry EuroCord to achieve consistent production of high quality cord blood products that will comply with NetCord-FACT standards.
Keywords: hematologija; matične celice; popkovnična kri